Clinical phenotype of the 16p.13.11 microdeletion: a case report with a mini review of the literature - Palumbi, Roberto; Ponzi, Emanuela; Micella, Stefania; Pascali, Mara; Bucci, Roberta; Gentile, Mattia; Margari, Lucia; Simone, Marta (Frontiers in Genetics, 2024)
Background: Chromosome 16p13.11 microdeletion is a very rare copy number variant (CNV), associated with a clinical syndrome characterized by global development delay, neuropsychiatric conditions, facial dysmorphisms, microcephaly, gastroesophageal reflux disease, and congenital heart defects. The 16p13.11 locus is a very unstable genomic region, rich in low-copy number repeats, characterized by many homologous DNA sequences. Usually, the most common CNV of this region include microduplications/duplications, while the microdeletions are very rare, and their clinical features are heterogeneous and poorly described so far.In this paper, we report the genetic and the clinical features of a patient diagnosed with chromosome 16p13.11 microdeletion, and a short review of the literature on this topic. Our patient was characterized by several facial dysmorphic features, autistic symptoms and language development delay. The genetic evaluation revealed and interstitial deletion of the long arm of the chromosome 16, approximately of 1.5 Mb.Interestingly, compared to previous cases, this patient was characterized by autistic symptoms, severe language and motor coordination disorder, without cognitive and cerebral malformations, frequently associated with this microdeletion syndrome.Interestingly, compared to previous cases, our patient was characterized by a severe language development disorder, few autistic symptoms and motor coordination development, without cognitive impairment, brain malformations or epileptic features, frequently associated with this microdeletion syndrome.